The Effects of Oil Price on the Korean Economy: A Global VAR Approach. Issue 5 (9th April 2018) - Park, Hail; Shin, Yongcheol
ABSTRACT: This article empirically explores the effects of oil price on the Korean economy using a Global VAR model. First, we evaluate the average connectedness of oil price with the Korean domestic variables over the precrisis period. We then investigate the time-varying contribution of oil price to the Korean financial and real sectors during and after the global financial crisis through recursive estimation. It is found that the contribution of oil price becomes very large in the case of real exports, equity prices, and real output, but plays a much less prevalent role in the remaining cases. In the meantime, the time-varying contribution of oil price to the Korean economy has not changed during and after the global financial crisis. Interestingly, we find that the Korean economy is affected mostly by overseas financial conditions in the short-term but it becomes more susceptible to oil price fluctuations in the long run, suggesting that Korea's reliance on energy imports leaves the economy exposed to volatility in energy prices.